Psychological Problems Experienced by Patients with Bowel Endometriosis Awaiting Surgery - Helizabet Salomão Abdalla Ayroza Ribeiro; Andresa Maria Felipe de Paiva; Beatriz da Costa Porto Taliberti; Anna Luiza Lobão Gonçalves; Renata Pereira Condes; Paulo Augusto Galvão Ayroza Ribeiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To assess the most common psychological disturbances in women with deep endometriosis and bowel involvement who are waiting surgical treatment and to evaluate what forms of coping are used to solve the problem. Methods This was a cross-sectional observational study of 40 women diagnosed with deep endometriosis and intestinal symptoms. They completed two questionnaires: one for anxiety and depression (Hospital Anxiety and Depression Scale [ HADS]) and the Scale of Mode of Confronting Problems (EMEP, in the Portuguese acronym). Results We found that 77.1% of the patients had anxiety and depression, with anxiety being the most prevalent (87.5% of the patients); 90% of the patients used problem focused and religious introspection as their main modes of confronting problems. Conclusion In the use of the HADS questionary, two psychological aspects were the most present in women with deep endometriosis awaiting surgical treatment: anxiety and depression. The most used forms of coping to solve the problem were problem coping and religious practices.